Legal Pluralism and Structural Injustice: Minority Rights and Human Rights Governance in Southeast Asia - Farid Mat Zin (Journal Discrimination and Injustice, 2026)
This article examines the persistent gap between constitutional commitments to equality and the socio-legal realities experienced by minority groups under plural legal orders in Southeast Asia, with Indonesia as the main case. It aims to explain how legal pluralism formed through state law, customary authority, religious norms, regional policies, and administrative discretion—can reproduce structural injustice rather than protect diversity. Using structural injustice theory, critical legal pluralism, substantive equality, and human-rights-based governance, this study applies a qualitative socio-legal approach through systematic document analysis of constitutional provisions, legislation, regional regulations, judicial decisions, policy documents, human rights reports, and relevant academic studies. The findings show that legal pluralism becomes discriminatory when fragmented authority enables administrative gatekeeping, majority approval, deviance labeling, selective enforcement, weak legal aid, and inconsistent judicial protection. Minority rights are therefore often recognized formally but remain difficult to convert into effective remedies. The article recommends reorienting legal pluralism toward human-rights-based governance through substantive equality review, stronger oversight of local regulations, accountable administrative procedures, accessible legal aid, and judicial reasoning that prioritizes non-discrimination over majoritarian pressure. This framework contributes to inclusive public policy and minority protection in societies.